2010
DOI: 10.1007/s12237-010-9360-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Relative Predation Vulnerability Between Native and Non-native Oyster Larvae and the Influence on Restoration Planning in an Estuarine Ecosystem

Abstract: The costs and benefits of non-native introductions as a restoration tool should be estimated prior to any action to prevent both undesirable consequences and waste of restoration resources. The suggested introduction of nonnative oyster species, Crassostrea ariakensis, into Chesapeake Bay, USA, provides a good example in which the survival of non-native oysters may differ from that of native oysters, Crassostrea virginica, during the larval stage. Experiments were conducted to compare the predation vulnerabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…If swimming activity incurs costs, e.g. increased predation risk [ 63 ], an option may be to increase swimming velocity only within the envelope of a waterborne cue and thus enhance encounter rate with the substrate when swimming through the boundary layer. Although Chan et al [ 64 ] recently showed that gastropod larvae significantly modify the swimming velocity through adjustment of velum extension there is yet no information about this mechanism in shipworm larvae or in response to a chemical cue.…”
Section: Discussionmentioning
confidence: 99%
“…If swimming activity incurs costs, e.g. increased predation risk [ 63 ], an option may be to increase swimming velocity only within the envelope of a waterborne cue and thus enhance encounter rate with the substrate when swimming through the boundary layer. Although Chan et al [ 64 ] recently showed that gastropod larvae significantly modify the swimming velocity through adjustment of velum extension there is yet no information about this mechanism in shipworm larvae or in response to a chemical cue.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental changes affect species in many different ways, altering their productivity and interactions with other species and understanding these effects of ecosystems is a challenge for research management (Breitburg et al 1999;Harrington et al 1999). Intentional changes for ecosystem management represent an investment to improve ecosystem services, such as fishing or aquaculture production, but can also pose risk interactions between native and non-native species and it may have unintentional consequences on the environment (Fulford and Breitburg 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This occurs through the production of mucoidal pseudofaeces, which converts predominantly sandy substrata into mud-dominated substrata with a high organic content that rapidly becomes anoxic and unsuitable for other species (Streftaris & Zenetos, 2006). This includes oysters that prefer less silty and muddy waters (Barnes et al, 1973;Bromley, McGonigle, Ashton, & Roberts, 2016;Fulford, Breitburg, & Luckenbach, 2011;Walne, 1979).…”
Section: And the Pacific Oystermentioning
confidence: 99%
“…This occurs through the production of mucoidal pseudofaeces, which converts predominantly sandy substrata into mud‐dominated substrata with a high organic content that rapidly becomes anoxic and unsuitable for other species (Streftaris & Zenetos, 2006). This includes oysters that prefer less silty and muddy waters (Barnes et al, 1973; Bromley, McGonigle, Ashton, & Roberts, 2016; Fulford, Breitburg, & Luckenbach, 2011; Walne, 1979). Ostrea edulis populations are also negatively impacted through a reduction in suitable substrata available for larval settlement (Blanchard, 1997), hindering recruitment and potentially oyster restoration efforts on the seabed.…”
Section: Introductionmentioning
confidence: 99%